Experience Numerous benefits of Water-based activity in The Island of God - Rizky Januar (Bali Tourism Board, 2019)
Starting to do exercise must be challenging, especially for someone who is not used to it. Therefore, combining physical activity and vacation is a perfect option for a beginner. Water sport may be a perfect choice to spend a holiday while train body back into its perfect condition. A getaway trip to Bali Is not only about staying in luxury hotels or villas, Wine and dine on a famous beachfront restaurant, or shopping in the heart of Seminyak shopping centers. The exotic island on the equator offers a wide selection of water recreation with dozen of benefits for those health seekers. This writing is a descriptive study. The findings from previous studies which discussing vacation and water-related exercise were compiled as data. Bali was served as tourism object where this study is undertaken. Then, the compiled data were used to describe the benefit of recreation in Bali as the tourism object and its water activity for health. The Island of Bali, known for its breathtaking landscape and as the best tourist destination, offers additional choices to tourists who wished to travel while getting extra benefits for their health. Some studies revealed there are numerous advantage someone may obtain by doing physical activity in the water, such as improvement in cardio, respiratory, and muscle strength. The activity also promotes full body workout to help overcome weight problem, both under and overweight while holiday in Bali helps the traveler to take a break from the tedious yet stressful environment.